New Vertical-Seam Type Double-Pond Fishway Design and Hydraulic Characteristics Analysis - XIE Meiling; FU Chenghua; WU Yijie (Renmin Zhujiang)
Fishway is an important channel to ensure the survival and reproduction of fish and enable migratory aquatic organisms to pass through obstacles such as dams and sluices.A new vertical-seam type double-pond fishway is designed,and the RNG κ-ε model is used to numerically simulate the fishway and calculate its hydraulic characteristics for analysis.The results show that the fishway has three mainstream areas and multiple stable recirculation areas with low flow velocity,and the indoor water flow of the fishway pond has rich flow velocity information,which can provide upstream information for different fish to help them migrate.In addition,the turbulent kinetic energy of the recirculation areas in the rest pond is small and stable along the course,and the maximum turbulent kinetic energy of the stilling basin is.As a new type of fishway,the vertical-seam type double-pond fishway can easily meet the migratory conditions of fish in terms of its hydraulic characteristics,and the relevant results can provide a reference for the engineering design of the fishway.